PEMENTASAN TARI SAKRAL BARIS CINA SEBAGAI SALAH SATU DAYA TARIK WISATA DI DESA SUMAWANG SANUR - Gede Agus Jaya Negara; I Nyoman Ariyoga (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Sumawang Village is one of the villages in the Sanur area which is famous for having beautiful beaches, because of the beauty of this beach, the Sanur area is famous for being one of the tourism destinations in the city of Denpasar. But that's not all, the tourism destinations in the Sanur area, precisely in the village of Sumawang, in this village there is a sacred dance whose performances are only performed on certain days such as during piodalan, masterpieces or the occurrence of a disease outbreak that attacks this village. This dance is called the Baris Cina dance, from its name we can know that this dance is a cultural acculturation that occurs between Chinese culture and local culture, we can see from its characteristics such as the clothes used by the dancers, the dance movement looks like an art movement martial arts from the Chinese region and songs that use Chinese, Arabic and Balinese to accompany this dance.In this study, using an empirical approach with qualitative descriptive methods and data collection techniques by means of a literature study and ended with a data analysis process.The purpose of this research is to find out other tourism potentials in the Sumawang Sanur village area apart from the beach tourism destinations.